2015
DOI: 10.1038/nature15258
|View full text |Cite
|
Sign up to set email alerts
|

Alternative transcription initiation leads to expression of a novel ALK isoform in cancer

Abstract: Activation of oncogenes by mechanisms other than genetic aberrations such as mutations, translocations, or amplifications is largely undefined. Here we report a novel isoform of the anaplastic lymphoma kinase (ALK) that is expressed in ~ 11% of melanomas and sporadically in other human cancer types, but not in normal tissues. The novel ALK transcript initiates from a de novo alternative transcription initiation (ATI) site in ALK intron 19, and was termed ALKATI. In ALKATI-expressing tumours, the ATI site is en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
244
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 206 publications
(274 citation statements)
references
References 39 publications
10
244
1
3
Order By: Relevance
“…Exome sequencing studies have shown that approximately 50% of resistant tumors harbor secondary mutations that reactivate the MAPK/ERK pathway (5,40). Nonmutational mechanisms that govern drug sensitivity are not fully understood and can involve reversible cellautonomous or microenvironment-mediated tuning of MAPK/ ERK pathway activity (8,9,(41)(42)(43). The strength of coupling between upstream MAPK/ERK signaling and the downstream transcriptional response can modulate the MAPK inhibitor response, as failure to turn off transcription in response to MAPK inhibition may increase drug tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Exome sequencing studies have shown that approximately 50% of resistant tumors harbor secondary mutations that reactivate the MAPK/ERK pathway (5,40). Nonmutational mechanisms that govern drug sensitivity are not fully understood and can involve reversible cellautonomous or microenvironment-mediated tuning of MAPK/ ERK pathway activity (8,9,(41)(42)(43). The strength of coupling between upstream MAPK/ERK signaling and the downstream transcriptional response can modulate the MAPK inhibitor response, as failure to turn off transcription in response to MAPK inhibition may increase drug tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…1) Recently, the truncated isoform of ALK (ALK ATI ) was reported to localize to the nucleus as well as cytoplasm, but its nuclear role was not clarified. 13) Therefore, in the present study, we analyzed its role in the nucleus. We found that nuclear ALK ATI induces chromatin structural changes and heterochromatinization.…”
Section: Discussionmentioning
confidence: 99%
“…13) In order to confirm this finding, we transiently expressed ALK-FL and ALK ATI in HeLa S3 cells (Figs. 1A, B).…”
Section: Alkmentioning
confidence: 99%
See 2 more Smart Citations